Design of remote monitoring system for interior environmental parameters of yacht. Issue 5 (April 2019) - Wang, Xiaozhen; Xiao, Qijun; Bai, Lu; Wu, Pianhui; Luo, Zhonghui
Abstract: Aiming at the yacht equipment and personal safety, as well as the yachtowner and water management departments should grasp the yacht related state in time, it is designed in this paper the remote monitoring system for yacht cabin environment parameters based on ZigBee and GPRS technology. The work mainly includes the structure of network system and the network topology design, as well as system hardware design, software design, and simulation experiment to realize the remote real-time data display, analysis and storage. The simulation test shows that the system can monitor the internal environment parameters of the yacht in real time. The system runs stably and has good expansion performance. The relative error of the system measurement is no more than 1.52%.